ANALISIS YURIDIS KEPASTIAN HUKUM PERJANJIAN PENGIKATAN JUAL BELI (PPJB) ATAS TANAH - Mugiati Mugiati (Universitas Suryakancana, 2022)
The agreement of binding and buying and selling (PPJB) in a sale and purchase transaction on land, resulting from the sale and purchase of the land there are conditions stipulated in the land law are not fulfilled by the parties who buy and sell the land. Research results: The agreement on the sale and purchase of land based on land law has the same legal position as ordinary agreements in general, namely the rights and obligations of the parties and make laws for the parties, but have not transferred property rights to land juridically as stipulated in Article 19 paragraph (1) of the Agrarian Law as the basis for realizing legal certainty and its implementation through Government Regulation No. 24 of 1997 concerning Land Registration as the basis of regulations in terms of use, utilization, ownership and legal actions related to land, so that the land sale and purchase agreement has not provided legal certainty over the right to property on the land. Juridically the land sale and purchase agreement is felt to be weak or not strong, because if there is a dispute over the land, then the party who holds the deed of the land sale and purchase agreement cannot prove the right of ownership of the land, because there has not been a transfer of land rights.Keywords: Land Rights, Legal Certainty, Land Registration, Agreement Sale and Purchase Binding (PPJB).